Cinzas das Folhas de Bambu: Material Cimentício Suplementar Sustentável - Silva, Lucas Henrique Pereira (2024)
The occurrences of climate change and natural disasters in recent years have compelled humanity to explore more sustainable ways of living. To achieve this, it is imperative to find productive alternatives that demand fewer natural resources and result in less pollution. The production of cement causes significant environmental impacts through the emission of greenhouse gases, which has prompted research into alternative materials that are less polluting. Looking into the past, a primitive form of cement called pozzolanic material can be found. Nowadays, pozzolanic materials are present in various cements and offer technical advantages, such as greater resistance in aggressive environments. Notable among pozzolanic materials are certain residues like blast furnace slag and fly ash. The search for new materials is crucial to meet growing and localized demands. Bamboo leaf ash (BLA) is a relatively new material that has gained attention. In this context, a systematic literature review was conducted to identify the state of the art and significant knowledge gaps. From this point, two gaps were investigated: 1- The efficiency of internal curing in mortars composed of bamboo leaf ash. In this chapter, carbopol 940 (C940) was used as a superabsorbent polymer (SAP) in quantities of 0.1%, 0.2%, and 0.3% relative to the cement mass. The pre-swollen SAP was incorporated into mortars where cement was replaced by 12.50% and 25% of CFB. Various tests were conducted to characterize the materials and mortars produced. The results showed that CFB exhibited the necessary reactivity for use as a pozzolanic material. However, C940 did not have the ideal physical characteristics to be used as an SAP in cementitious materials, leading to a decrease in the compressive strength of the tested mortars. 2- The durability of mortars composed of 20%, 25%, 30%, and 40% CFB was evaluated in terms of compressive strength, electrical resistivity, resistance to chloride migration and diffusion, and carbonation. The mechanical test demonstrated comparable compressive strength of mortars with the reference, even with higher levels of cement replacement (30% and 40% CFB). Electrical resistivity indicated that higher amounts of CFB resulted in a denser cementitious matrix. Results from tests on chloride attack resistance, evaluated against migration and diffusion, showed better performance of composite mortars. The migration coefficient of the mortar with 40% CFB was 5.75 times lower than that of the reference mortar. The obtained data demonstrated that CFB could be an excellent alternative supplementary cementitious material where this residue from other production chains is available, bringing improvements in durability and reducing building maintenance costs.